TATA KELOLA SIAKAD SEKOLAH MENENGAH ATAS NEGERI 7 BANDAR LAMPUNG BERBASIS WEB MOBILE - Puspitasari, Tuti; Rustam, Rustam; Muslihudin, Muhamad (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2023)
This research was conducted to overcome the problem of the lack of the role of technology in high schools. Researchers used the method of observation and interviews with stakeholders in schools, as well as using the SDLC design model. In making the school information system, researchers used several programming languages, such as HTML, CSS, PHP, and MySQL as data storage (databases). The main objective of this research is to create a school information system that can assist schools, staff, and teachers in managing student and teacher data. This system is expected to facilitate activities in schools and reduce errors in data management. The school information system created by the researcher includes several features, such as student data management, teacher data management, inputting student grades, class schedules, and tuition payment services that are connected directly to the treasurer. All of these features are designed to make it easier for schools to manage various important data, especially teacher and student data. Researchers also pay attention to aspects of data security and privacy in making school information systems. Therefore, this system is equipped with user authentication and authorization features as well as an automatic data backup system. It is hoped that with a school information system created by researchers, schools can be more effective and efficient in managing teacher and student data, and can optimize business processes in schools. In addition, with the technology applied in schools, it is hoped that it can improve the quality of education in schools and prepare students to face future challenges.